A method for estimating the area of damaged croplands and woodlands with the use of unmanned aerial vehicles (drones) - Podciborski, Tomasz; Kil, Jacek (International Conference “Environmental Engineering”, 2017)
Growing social demand for access to spatial information spurs the rapid development of measurement methods and systems for registering the results of spatial evaluations and analyses (Kwietniewski 2008). Any assessment of spatial development is carried out on the basis of information obtained from specific sources (Kowalczyk 2007). The main objective of this study was to propose a method for assessing the extent of damage caused by natural disasters to croplands and woodlands with the use of unmanned aerial vehicles (drones). The main aim was achieved through detailed goals, including determination of the causes of natural disasters, description of the field inspection procedure and development of loss assessment principles. The proposed method was verified in selected research sites, and the resulting damage report detailing cropland losses is presented in the study.